2022
DOI: 10.3390/toxics10110643
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation, Source Identification, and Cancer Risk Assessment of Polycyclic Aromatic Hydrocarbons (PAHs) in Different Jordanian Vegetables

Abstract: The accumulation of polyaromatic hydrocarbons in plants is considered one of the most serious threats faced by mankind because of their persistence in the environment and their carcinogenic and teratogenic effect on human health. The concentrations of sixteen priority polycyclic aromatic hydrocarbons (16 PAHs) were determined in four types of edible vegetables (tomatoes, zucchini, eggplants, and cucumbers), irrigation water, and agriculture soil, where samples were collected from the Jordan Valley, Jordan. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…An increased risk of stomach or gastrointestinal cancer has also been reported in the general population in association with smoked or grilled foods, such as fish and meat products, that become contaminated with PAHs during preparation (4,5,9). In addition, Al-Nasir et al (10) suggested that the consumption of vegetables grown in areas where the soil is contaminated with PAHs may pose a potentially higher risk of cancer and affect human health. In addition to a direct mutagenic effect, reduced efficiency of DNA repair mechanisms has been reported in individuals exposed to PAHs, and the magnitude of this negative effect may be influenced by genetic polymorphism (11).…”
Section: Introductionmentioning
confidence: 96%
“…An increased risk of stomach or gastrointestinal cancer has also been reported in the general population in association with smoked or grilled foods, such as fish and meat products, that become contaminated with PAHs during preparation (4,5,9). In addition, Al-Nasir et al (10) suggested that the consumption of vegetables grown in areas where the soil is contaminated with PAHs may pose a potentially higher risk of cancer and affect human health. In addition to a direct mutagenic effect, reduced efficiency of DNA repair mechanisms has been reported in individuals exposed to PAHs, and the magnitude of this negative effect may be influenced by genetic polymorphism (11).…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, tap water intake is an important source of human exposure to a variety of pollutants, such as organophosphate flame retardants and bisphenol analogues [30][31][32]. For the general population, the uptake of some pollutants through plants that are irrigated by contaminated water should also be a concern [33][34][35]. Considering the wide presence of PPDs in environmental surface water, PPDs may occur in tap water sources, such as freshwater rivers and reservoirs [11,36].…”
Section: Introductionmentioning
confidence: 99%
“…9 Over 90% of PAHs are persistent in the environment, and plants growing in the contaminated area are easily exposed to the whole group of PAHs and are contaminated via absorption. 1,10 Discerning the mechanism of uptake and transduction of PAHs by plants is of great importance to assessing their fate and food safety. In recent decades, environmental scientists have shown considerable interest in these mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Plants play a pivotal role within the terrestrial food web as primary producers, providing the initial source of energy for all life forms . Over 90% of PAHs are persistent in the environment, and plants growing in the contaminated area are easily exposed to the whole group of PAHs and are contaminated via absorption. , Discerning the mechanism of uptake and transduction of PAHs by plants is of great importance to assessing their fate and food safety. In recent decades, environmental scientists have shown considerable interest in these mechanisms. , Their research confirms that plant surfaces efficiently absorb these pollutants and PAHs enter plants mainly through foliar and root uptake pathways.…”
Section: Introductionmentioning
confidence: 99%